CONTENT ANALYSIS OF ESG IMPLEMENTATION IN MAJOR ISLAMIC BANKING IN SELECTED OIC COUNTRIES - Roisatun Kasanah; Nuzulia Nuzulia; Muhammad Anis; Dahruji Dahruji (Universitas Airlangga, 2026)
Despite the growing alignment between ESG principles and Islamic finance values, empirical evidence on the depth and consistency of ESG disclosure among major Islamic banks across OIC countries remains limited, particularly in the post-COVID period marked by heightened sustainability pressures. This study addresses this gap by examining the extent and pattern of ESG disclosure among six major Islamic banks in OIC countries through qualitative content analysis of their 2023 sustainability reports, evaluated against the Global Reporting Initiative (GRI) Standards. The novelty of this study lies in its systematic cross-country comparison of Islamic bank ESG disclosure using GRI as a unified analytical framework. The results reveal significant disparities across banks and dimensions: Bank Syariah Indonesia leads overall disclosure with 73 indicators, while Al Rajhi Saudi Arabia discloses only 19. Critical social and environmental indicators, including human rights assessment, socioeconomic compliance, and supplier environmental screening remain unreported across all six banks, highlighting a systemic gap between the normative aspirations of Islamic finance and actual reporting practice. These findings underscore the urgent need for harmonized ESG reporting standards across OIC jurisdictions and provide actionable insights for regulators, Islamic banks, and investors seeking to strengthen the integrity and credibility of sustainability reporting within the Islamic financial system. Future studies are encouraged to expand the sample size, incorporate longitudinal analysis to track disclosure progress over time, and explore the institutional and regulatory determinants that drive variation in ESG reporting quality among Islamic financial institutions globally.